2015
DOI: 10.1105/tpc.15.00102
|View full text |Cite
|
Sign up to set email alerts
|

Structural Mechanism Underlying the Specific Recognition between the Arabidopsis State-Transition Phosphatase TAP38/PPH1 and Phosphorylated Light-Harvesting Complex Protein Lhcb1

Abstract: During state transitions, plants regulate energy distribution between photosystems I and II through reversible phosphorylation and lateral migration of the major light-harvesting complex LHCII. Dephosphorylation of LHCII and the transition from state 2 to state 1 requires a thylakoid membrane-associated phosphatase named TAP38 or PPH1. TAP38/PPH1 specifically targets LHCII but not the core subunits of photosystem II, whereas the underlying molecular mechanism of their mutual recognition is currently unclear. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 52 publications
(70 reference statements)
1
43
0
Order By: Relevance
“…For PPM phosphatases, the closely-spaced M1-M2 cluster provides a highly specific binding environment for phosphate ions, pSer-and pThr-peptides, and phosphoprotein substrates (6,12,21). The requirements for specific binding of phosphoproteins are distinct from requirements for catalytic activity, as specific binding of substrates was observed by catalytically inactive mutants that preserve the M1-M2 cluster or in the presence of Ca 2+ ions, as reported previously (29,33,37) and in the present work. The M1 and M2 ions jointly coordinate a bridging water molecule/hydroxide ion that has been proposed to function as the nucleophile in the S N 2 phosphate monoester hydrolase reaction (6,12,21).…”
supporting
confidence: 53%
See 3 more Smart Citations
“…For PPM phosphatases, the closely-spaced M1-M2 cluster provides a highly specific binding environment for phosphate ions, pSer-and pThr-peptides, and phosphoprotein substrates (6,12,21). The requirements for specific binding of phosphoproteins are distinct from requirements for catalytic activity, as specific binding of substrates was observed by catalytically inactive mutants that preserve the M1-M2 cluster or in the presence of Ca 2+ ions, as reported previously (29,33,37) and in the present work. The M1 and M2 ions jointly coordinate a bridging water molecule/hydroxide ion that has been proposed to function as the nucleophile in the S N 2 phosphate monoester hydrolase reaction (6,12,21).…”
supporting
confidence: 53%
“…The structural comparison of the free and substrate-bound forms of the PPM1A catalytic domain and the analysis of sequence variation among metazoan homologues support the importance of the first few N-terminal residues, the α2-β5 bridge, and the Flap subdomain in interactions between the enzyme and substrate. Recently, crystal structures of the Arabidopsis thaliana PP2C phosphatase TAP38/PPH1 in the free state and as the D180E mutant in complex with a phosphothreonine-peptide substrate were described (37). Similar to conformational changes of PPM1A residues R33 and R186 described above, the conformations of the TAP38/PPH1 residues R69 and R225 are altered upon binding of the substrate (37).…”
Section: Comparison Of Phosphate-bound and Cyclic Peptide-bound Formsmentioning
confidence: 74%
See 2 more Smart Citations
“…Under these conditions the redox state of the photosynthetic PQ pool is altered and the Stt7/STN7 is instrumental in maintaining a proper plastid redox poise. Moreover, this kinase appears to be the major regulator of the phosphorylation of the LHCII proteins because there is no evidence that the activity of the PPH1/TAP38 phosphatase, the counteractor of STN7, is regulated, suggesting that it is constitutively active (Shapiguzov et al, 2010;Wei et al, 2015). Our study has revealed new features of the Stt7/STN7 protein kinase that have to be taken into account for modeling this activation process.…”
Section: Discussionmentioning
confidence: 99%